Cancer of the Esophagus - Endoscopic Ultrasound: Selection for Cure - Giancarlo Caletti; Paolo Bocus; Pietro Fusaroli; Thomas Togliani; Gregary Marhefka; Enrico Roda (Canadian Journal of Gastroenterology)
Several treatment options are available to treat esophageal cancer. Ideally, treatment should be individualized, based on the projected treatment outcome for that individual. Accurate staging of the extent of the disease at the time of diagnosis offers the most rational attempt at stratifying patients into categories that can be used to affect treatment choices. Endoscopic ultrasonography (EUS) is the most accurate nonoperative technique for determining the depth of tumour infiltration and thus is accurate in predicting which patients will be able to undergo complete resection. EUS is also being used for tumour staging in order to guide treatment decisions in patients with esophageal cancer.